A Study of Radicalism in Hare's Fanshen and Foucault's Dynamics of Power: Irrationalism and the Absence of Possibilities - Siamak Shahabi; Bahee Hadaegh (Critical Literary Studies)
This study pursues a study of radicalism in Hare’s most radical play, Fanshen, and in Foucault’s mode of radicalism within his theory of power relations. From a specific perspective, this study borrows from the new wave of reevaluating and reinterpreting Foucault, which is concerned with irrationalism in his mode of radicalism. This analysis helps us comprehend the changes in the social trends and the specific pattern of radicalism in both Hare and Foucault. What concerns this study gravely, is the absence of the other side of reality or possibility in Hare’s Fanshen and in Foucault’s claims on power relations. The aim of the study is to depict how adopting radicalism and revolution by Hare and Foucault results in the justification of malfunctioned experiments. Furthermore, the way political tendencies are manifested to the audience is proved to be a key factor in the analysis of British political theater and in the shaping of British society. Finally, it is found that a Foucauldian reading of Fanshen results in the recognition of Hare’s specific pattern of radicalism which is in line with Foucault’s.